USP10 deletion inhibits macrophage-derived foam cell formation and cellular-oxidized low density lipoprotein uptake by promoting the degradation of CD36 - Xia, Xiaohong (Aging (Albany NY), 2020)
Foam cell formation process is involved in the pathogenesis of atherosclerosis (AS). Activation of this biological process depends on lipid uptake by scavenger receptors, such as CD36, SR-A and SR-B1. Among these receptors, CD36 is the principal one because it dominates roughly 50% lipid uptake in monocytes. In this study, our western blotting and RT-qPCR assays revealed that USP10 inhibition promotes the degradation of CD36 protein but does not change its mRNA level. In addition, Co-IP results showed that USP10 interacts with CD36 and stabilizes CD36 protein by cleaving poly-ubiquitin on CD36. Significantly, USP10 promotes foam cell formation. Immunofluorescence and Oil red O staining assays show that inhibition or knockdown of USP10 suppresses lipid uptake and foam cell formation by macrophages. In conclusion, USP10 promotes the development and progression of atherosclerosis through stabilizing CD36 protein expression. The regulation of USP10-CD36 may provide a significant therapeutic scheme in atherosclerosis.